PERSPEKTIF LAW AS AN ALLOCATIVE SYSTEM UNDANG-UNDANG OTORITAS JASA KEUANGAN - darmawan, agus (FIAT JUSTISIA, 2014)
Based on Friedmans point of view, search for secondary data in this research aims to provide an academic evaluation (assessment), the law as an allocative system against Law on Financial Services Authority. By using a normative approach, it can be concluded that the Law on Financial Services Authority academically has fulfilled the legal criteria for allocative system as intended by Friedman.Â  Establishment of the Financial Services Authority (FSA) is intended as an independent agency that oversees the financial services sector of Indonesia, to strengthen accountability, transparency, and credibility of Bank Indonesia without diminishing the independence of state institutions, and policy making by the central bank will not be affected by the FSA, since the FSA served to increase oversight of financial institutions for the better.Â Keywords: law, allocative system and financial services authority.